(untitled) (Global Journals of Research in Engineering, 2023)
In order to design a microporous membrane filter comprising Three-way Catalyst TWC particles with a size distribution of 1 to 2 microns isothermal CO oxidation experiments and numerical simulations were conducted to investigate the transport of oxygen atoms within primary Ceria-Zirconia CZ particulates These spherical TWC particles were fabricated through the agglomeration of primary CZ and alumina particulates incorporating Pd and Rh catalysts By comparing experimental CO2 emissions with simulation results over time a temperature-dependent diffusion coefficient was determined The simulation results reveal that the effective distance of oxygen atom transport within CZ particulates heterogeneously distributed in the spherical TWC particle is limited to approximately 100 nm from the surface of agglomerated spherical TWC particles within a temperature range of 175 to 225 C